MAIT Cells at the Fetal-Maternal Interface During Pregnancy - Kaipe, Helen; Raffetseder, Johanna; Ernerudh, Jan; Solders, Martin; Tiblad, Eleonor (Frontiers in Immunology, 2020)
One of the main functions of the human placenta is to provide a barrier between the fetal and maternal blood circulations, where gas exchange and transfer of nutrients to the developing fetus take place. Despite being a barrier, there is a multitude of crosstalk between maternal immune cells and fetally derived semi-allogeneic trophoblast cells. Therefore, the maternal immune system has a difficult task to both tolerate the fetus but at the same time also defend the mother and the fetus from infections. Mucosal-associated invariant T (MAIT) cells are an increasingly recognized subset of T cells with anti-microbial functions that get activated in the context of non-polymorphic MR1 molecules, but also in response to inflammation. MAIT cells accumulate at term pregnancy in the maternal blood that flows into the intervillous space inside the placenta. Chemotactic factors produced by the placenta may be involved in recruiting and retaining particular immune cell subsets, including MAIT cells. In this Mini-Review, we describe what is known about MAIT cells during pregnancy and discuss the potential biological functions of MAIT cells at the fetal-maternal interface. Since MAIT cells have anti-microbial and tissue-repairing functions, but lack alloantigen reactivity, they could play an important role in protecting the fetus from bacterial infections and maintaining tissue homeostasis without risks of mediating harmful responses towards semi-allogenic fetal tissues.